Strengths and Weaknesses of Cell Synchronization Protocols Based on Inhibition of DNA Synthesis - Ligasová, Anna; Koberna, Karel (International journal of molecular sciences, 2021)
Synchronous cell populations are commonly used for the analysis of various aspects of cellular metabolism at specific stages of the cell cycle. Cell synchronization at a chosen cell cycle stage is most frequently achieved by inhibition of specific metabolic pathway(s). In this respect, various protocols have been developed to synchronize cells in particular cell cycle stages. In this review, we provide an overview of the protocols for cell synchronization of mammalian cells based on the inhibition of synthesis of DNA building blocks-deoxynucleotides and/or inhibition of DNA synthesis. The mechanism of action, examples of their use, and advantages and disadvantages are described with the aim of providing a guide for the selection of suitable protocol for different studied situations.
Keywords: Humans; buněčné dělení; Cell Division; ribonucleotide reductase; thymidine; DNA replication; Cell Cycle; lidé; replikace DNA; deoxyribonucleotide triphosphates synthesis; thymidylate synthase; Animals; S phase; DNA Replication; DNA; zvířata; buněčný cyklus; cell cycle